Forecasting Penjualan Bahan Bangunan Menggunakan Metode Least Square Berbasis Website Menggunakan Framework Codeigniter - Febriyan Idil Adha; Asep Toyib; Armanto (Journal of Informatics Management and Information Technology, 2025)
The availability of stock information is crucial at Toko Jogja Bangunan considering the size and price of goods that are quite large and expensive. The problem that is often faced is running out of stock of certain items due to the lack of adequate sales and stock records. This results in decreased profits and high storage costs for unsold goods. This research aims to build a stock forecasting system using the Least Square method implemented through a Python-based application. The forecasting results are displayed in the form of tables and graphs, then validated manually based on previous sales data. The Least Square method was chosen because it is able to analyze random patterns, trends, seasonality, and cyclicality in sales data, and produce predictions with a low error rate. This forecasting system is implemented using the CodeIgniter framework to produce a web-based information system that is easily accessible and can present building material stock prediction reports accurately and quickly. With this system, it is hoped that Toko Jogja Bangunan can overcome shortcomings in stock management, improve operational efficiency, and support better decision making.